2012
DOI: 10.1007/s00253-012-4487-0
|View full text |Cite
|
Sign up to set email alerts
|

An Indian scenario on renewable and sustainable energy sources with emphasis on algae

Abstract: India is the fifth largest primary energy consumer and fourth largest petroleum consumer after USA, China, and Japan. Despite the global economic crisis, India's economy is expected to grow at 6 to 8 %/year. There is an extreme dependence on petroleum products with considerable risks and environmental issues. Petroleum-derived transport fuels are of limited availability and contribute to global warming, making renewable biofuel as the best alternative. The focus on biogas and biomass-based energy, such as bioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Algae are cultivated not only for food source but also the cultivated biomass is used for feedstocks too [6] and scaling up algae farming could lead to yields of other commercially viable products [7,8]. Since two thirds of earth's surface is covered with ocean, algae would be the option with greatest potential for food including aquaculture industries, pharma products and global energy needs ( Figure 1) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Algae are cultivated not only for food source but also the cultivated biomass is used for feedstocks too [6] and scaling up algae farming could lead to yields of other commercially viable products [7,8]. Since two thirds of earth's surface is covered with ocean, algae would be the option with greatest potential for food including aquaculture industries, pharma products and global energy needs ( Figure 1) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Lipids from microalgal origin appear as the most promising third-generation biodiesel feedstock. Microalgae have very high growth rates and accumulate high levels of lipids (oil) through photosynthesis [104,105]. Algal cultivation is easier than plant cultivation.…”
Section: Third Generation Feedstockmentioning
confidence: 99%
“…It is reported that, apart from biodiesel a microalgae biorefinery can produce various other biofuels such as biohydrogen, biogas, bioethanol, etc. Hemaiswarya et al [56] reported that microalgal biomass residue after lipid extraction can also be reused for methane production. Microalgae biomass remaining after lipid extraction can also be potentially used as feedstocks in food, feed, pharmaceutical, and cosmetic industries, etc., as shown in Figure 4 [56][57][58].…”
Section: Residual Biomass Management Which Remains After Lipid Extracmentioning
confidence: 99%
“…Hemaiswarya et al [56] reported that microalgal biomass residue after lipid extraction can also be reused for methane production. Microalgae biomass remaining after lipid extraction can also be potentially used as feedstocks in food, feed, pharmaceutical, and cosmetic industries, etc., as shown in Figure 4 [56][57][58]. There is limited applicability of such processes due to costly processes but the utilization of lipid-extracted microalgae biomass (LEMB) to produce different energy sources along with the extraction of high value-added products will make the microalgal biorefinery approach more inventive and economically plausible.…”
Section: Residual Biomass Management Which Remains After Lipid Extracmentioning
confidence: 99%